Cucumber Mosaic Virus Infection in Arabidopsis: A Conditional Mutualistic Symbiont? - Takahashi, Hideki; Tabara, Midori; Miyashita, Shuhei; Ando, Sugihiro; Kawano, Shuichi; Kanayama, Yoshinori; Fukuhara, Toshiyuki; Kormelink, Richard (Frontiers in microbiology, 2022)
A cucumber mosaic virus isolate, named Ho [CMV(Ho)], was isolated from a symptomless Arabidopsis halleri field sample containing low virus titers. An analysis of CMV(Ho) RNA molecules indicated that the virus isolate, besides the usual cucumovirus tripartite RNA genome, additionally contained defective RNA3 molecules and a satellite RNA. To study the underlying mechanism of the persistent CMV(Ho) infection in perennial A. halleri , infectious cDNA clones were generated for all its genetic elements. CMV, which consists of synthetic transcripts from the infectious tripartite RNA genomes, and designated CMV(Ho)tr, multiplied in A. halleri and annual Arabidopsis thaliana Col-0 to a similar level as the virulent strain CMV(Y), but did not induce any symptoms in them. The response of Col-0 to a series of reassortant CMVs between CMV(Ho)tr and CMV(Y) suggested that the establishment of an asymptomatic phenotype of CMV(Ho) infection was due to the 2b gene of CMV RNA2, but not due to the presence of the defective RNA3 and satellite RNA. The accumulation of CMV(Ho) 2b protein tagged with the FLAG epitope (2b.Ho-FLAG) in 2b.Ho-FLAG -transformed Col-0 did not induce any symptoms, suggesting a 2b-dependent persistency of CMV(Ho)tr infection in Arabidopsis . The 2b protein interacted with Argonaute 4, which is known to regulate the cytosine methylation levels of host genomic DNA. Whole genomic bisulfite sequencing analysis of CMV(Ho)tr- and mock-inoculated Col-0 revealed that cytosine hypomethylation in the promoter regions of 82 genes, including two genes encoding transcriptional regulators ( DOF1.7 and CBP1 ), was induced in response to CMV(Ho)tr infection. Moreover, the increased levels of hypomethylation in the promoter region of both genes, during CMV(Ho)tr infection, were correlated with the up- or down-regulation of their expression. Taken altogether, the results indicate that during persistent CMV(Ho) infection in Arabidopsis , host gene expression may be epigenetically modulated resulting from a 2b-mediated cytosine hypomethylation of host genomic DNA.